Adsorption of hexavalent chromium by polyacrylonitrile (PAN)-based activated carbon fibers from aqueous solution. Issue 32 (10th April 2015) - Jiang, Zhengjiang; Liu, Yunguo; Zeng, Guangming; Xu, Weihua; Zheng, Bohong; Tan, Xiaofei; Wang, Shufan
<x xml:space="preserve">Abstract</x> Polyacrylonitrile (PAN)-based activated carbon fibers (PAC400 and PAC600) were prepared by heating Zn(NO3)2 pretreated-PAN at 400 °C and 600 °C for the removal of Cr(vi) from aqueous solution.